Knowledge and attitude towards ankle sprain management among primary care physicians in the department of family medicine, King Fahad Armed Forces Hospital, Jeddah, Saudi Arabia - Abdullah A. Alzahrani; Norah A. AlQarni; Fahad S. Alghamdi; Tariq A. Alghamdi (Journal of Family Medicine and Primary Care)
Introduction: Family doctors are the primary care providers for ankle sprains, which are a prevalent condition that they treat with great care. Family physicians’ differing management styles and levels of knowledge about established recommendations may have a substantial influence on patient outcomes. Aims: The current study aimed to assess the level of awareness among family physicians regarding established guidelines for ankle sprain management. Materials and Methods: A cross-sectional study was conducted targeting all available and accessible primary care physicians within the Department of Family Medicine at King Fahad Armed Forces Hospital, Jeddah, Saudi Arabia during the period from 2023 to May 2024. Data were collected using an online questionnaire that was initiated by the study researchers after comprehensive review of similar articles in the literature. Results: A total of 88 primary care physicians were included. Physicians’ ages ranged from 25 to 60 years with a mean age of 33.4 ± 7.4 years old. A total of 47 (53.4%) were males, 29 (33%) were residents, 28 (31.8%) were consultants, 16 (18.2%) were senior Registrar, and 9 (10.2%) were GPs. A total of 41 (46.6%) of the study physicians had an overall good knowledge level about ankle sprain while most of them (53.4%) had poor knowledge level. A total of 55 (62.5%) of the study physicians utilize the Ottawa Ankle Rules to guide the need for X-ray imaging in ankle sprains, and 52 (59.1%) routinely provide information on preventive measures to patients diagnosed with an ankle sprain. Conclusion: The study found that primary care physicians have average knowledge about ankle sprains, diagnosis, classification, and treatment, with lower knowledge of follow-up plans. They need training and educational programs.